Motor learning triggers neuroplastic processes while awake and during sleep - Wenderoth, N. (Exercise and Sport Sciences Reviews, 2018)
Behavioral changes characteristic for motor learning result from synaptic plasticity within the sensorimotor system. This review summarizes how the central nervous system responds rapidly to motor activity while awake. It then discusses evidence for the hypothesis that sleep is essential for both stabilizing previously acquired motor memories and maintaining the brain`s efficacy to undergo plastic changes to learn new skills. ABSTRACT FROM AUTHOR